A Pan-Cancer Analysis Reveals CLEC5A as a Biomarker for Cancer Immunity and Prognosis - Chen, Rui; Wu, Wantao; Chen, Si-Yu; Liu, Zheng-Zheng; Wen, Zhi-Peng; Yu, Jing; Zhang, Long-Bo; Liu, Zaoqu; Zhang, Jian; Luo, Peng; Zeng, Wen-Jing; Cheng, Quan (Frontiers in Immunology, 2022)
Background: CLEC5A is a member of C-type lectin superfamily. It can activate macrophages and lead to a series of immune-inflammation reaction. Previous studies reveal the role of CLEC5A in infection and inflammation diseases. There also reports that CLEC5A differentially expresses in a few of cancer types and overexpression accompanies low overall survival of patients. However, the finding is limited to small sizes of cancer types, it remains more studies to verify the prognostic role of CLEC5A and the potential as a novel target for anti-tumor therapy. Method: We acquire and analyze data from TCGA database, GTEx database and other comprehensive databases via GSCALite, cBioPortal and TIMER 2.0 platforms or software. Results: CLEC5A differentially expresses between tumor and its adjacent normal tissue. DNA methylation mainly negatively correlates with CLEC5A expression. OS and CLEC5A expression level. SNV and CNV of CLEC5A exist in multiple cancers. Besides, CLEC5A is positively related to immune infiltration including macrophages, CAF and Tregs. Immune checkpoint gene significantly associates with CLEC5A expression in diverse cancer types. In addition, CLEC5A expression correlates with MMR in several cancers. TMB, MSI and neoantigens all show a positive association with CLEC5A expression in COAD and UCEC. Furthermore, the function enrichment analysis reveals the role of CLEC5A in cancer correlating to signal transduction and immune system as well as EMT and Apoptosis process. The drug sensitivity analysis provides potential therapeutic agents associated with CLEC5A expression including FR-180204, Tivozanib, OSI-930, Linifanib, AC220, VNLG/124, Bexarotene, omacetaxine mepesuccinate, narciclasine, leptomycin B, PHA-793887, LRRK2-IN-1 and CR-1-31B. Conclusion: CLEC5A overexpresses in multiple cancers in contrast to normal tissues and high expression of CLEC5A predicts poor prognosis of patients and immune infiltration as well as high drug sensitivity. These indicate that CLEC5A is potential as prognostic biomarker of diverse cancers and target for anti-tumor therapy. Key words: pan-cancer, CLEC5A, prognostic biomarkers, cancer immune, immunotherapy